2018
DOI: 10.1016/j.brs.2018.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral neuronavigated 20Hz theta burst TMS for treatment refractory depression: An open label study

Abstract: Bilateral Neuronavigated TBS-20Hz TMS brought more than two-thirds of treatment refractory depressed patients to remission. TBS-20Hz may be critical for obtaining higher remission rates. Controlled trials are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 9 publications
0
22
0
1
Order By: Relevance
“…28 Evidence showed that bilateral neuronavigationguided 20 Hz TBS TMS targeted on BA46 (−44, 40, and 29) and its right sided homolog (44, 40, and 29) brought more than twothirds of treatment refractory depressed patients to remission. 29 Here, our findings suggested that the neuronavigationguided 10 Hz rTMS targeted on BA46 could rapidly reduce suicidal ideation and mit igate depressive symptom. Further studies are needed to system atically explore whether the neuronavigation targeted method in rTMS treatment can result in superior therapeutic efficacy for pa tients with MDD in contrast to the conventional localization tech nique, such as "5cm method" and "10-20 method.…”
Section: Discussionmentioning
confidence: 58%
“…28 Evidence showed that bilateral neuronavigationguided 20 Hz TBS TMS targeted on BA46 (−44, 40, and 29) and its right sided homolog (44, 40, and 29) brought more than twothirds of treatment refractory depressed patients to remission. 29 Here, our findings suggested that the neuronavigationguided 10 Hz rTMS targeted on BA46 could rapidly reduce suicidal ideation and mit igate depressive symptom. Further studies are needed to system atically explore whether the neuronavigation targeted method in rTMS treatment can result in superior therapeutic efficacy for pa tients with MDD in contrast to the conventional localization tech nique, such as "5cm method" and "10-20 method.…”
Section: Discussionmentioning
confidence: 58%
“…Among the distinct frequencies, the now-standard 10 Hz rTMS for depression therapy has been widely accepted in clinical settings. Recent evidence suggests that active 5 Hz or 20 Hz rTMS may markedly improve clinical symptoms in depressed individuals when compared with sham rTMS ( George et al, 2000 ; Luborzewski et al, 2007 ; Philip et al, 2015 ; Stubbeman et al, 2018 ; Su et al, 2005 ). However, the primary limitations of 5 Hz or 20 Hz rTMS include modest clinical sample sizes and uncertain clinical safety and treatment tolerability ( Hadley et al, 2011 ; Loo et al, 2008 ; McGirr et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Aus Die Forschung im Bereich der Neurostimulation ist weiterhin dynamisch; es ist zu hoffen, dass durch die neuronavigierte Identifikation von Zielarealen eine noch genauere Applikation der Magnetimpulse erfolgen wird. Zudem steht mit der theta-burst-Behandlung ein Protokoll zur Verfügung, welches eine ähnliche antidepressive Wirksamkeit bei deutlich geringerer Behandlungszeit zeigt, was insbesondere für Patientengruppen wie Schwangere vorteilhaft sein könnte, da es den Nachteil der längeren Liegezeit vermindert [32][33][34].…”
Section: Introductionunclassified